2019
DOI: 10.3390/app9102114
|View full text |Cite
|
Sign up to set email alerts
|

Release of VEGF from Dental Implant Surface (IML® Implant) Coated with Concentrated Growth Factors (CGF) and the Liquid Phase of CGF (LPCGF): In Vitro Results and Future Expectations

Abstract: This study aimed to evaluate the combined use of the Concentrated Growth Factor (CGF) and the liquid phase of CGF (LPCGF) on dental implant surfaces, using a medical device to determine the migration of growth factors, from the implant surface to the recipient. The implants were permeated by autologous growth factors, using a specific centrifuge device. CGF adhesion on the implant surface was evaluated through a scanning electron microscope analysis. To assess the release of the vascular endothelial growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In a previous study, we showed that VEGF was released from titanium dental implant surfaces permeated with CGFs and containing fibrin, which is fundamental to accommodate the cellular network [ 38 ]. The present results show that CGFs with their soluble factors, including VEGF, and their cellular components, such as EPC-like cells, promoted neo-angiogenesis, suggesting that the incorporation of CGFs on dental implant surfaces could produce a biologically active area capable of promoting intercellular communication and neo-angiogenesis during bone regeneration and healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that VEGF was released from titanium dental implant surfaces permeated with CGFs and containing fibrin, which is fundamental to accommodate the cellular network [ 38 ]. The present results show that CGFs with their soluble factors, including VEGF, and their cellular components, such as EPC-like cells, promoted neo-angiogenesis, suggesting that the incorporation of CGFs on dental implant surfaces could produce a biologically active area capable of promoting intercellular communication and neo-angiogenesis during bone regeneration and healing.…”
Section: Discussionmentioning
confidence: 99%
“…Venous blood (8 mL) from 5 healthy, non-smoking adult donors, two females and three males, aged between 27 and 50 years old, was collected and immediately centrifuged by a Medifuge device (Medifuge MF200; Silfradent srl, Forlì, Italy), at 25 °C, using a program with the following characteristics: 30 s acceleration, 2 min 2700 rpm, 4 min 2400 rpm, 4 min 2700 rpm, 3 min 3000 rpm, and 36 s deceleration and stop, to obtain CGF clot, as previously described [ 36 , 38 ]. Informed consent was obtained from the donors included in this study in accordance with Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…PRF has shown enhancing effects on stem cell proliferation, differentiation, migration, and mineralization during bone formation [9,12,13]; however, PRF alone may have an unstable effect on osteogenesis in vivo [13]. CGF releases TGF-β, Vascular Endothelial Growth Factor (VEGF), Platelet-Derived Growth Factor (PDGF), Bone Morphogenetic Protein 2 (BMP2) and Insulin-like Growth Factor (IGF-1) [14][15][16] that increase proliferation and extracellular matrix mineralization via the BMP2/SMAD5/RUNX2 signaling pathway [6]. CGF also contains CD34 positive cells, fibroblasts, leukocyte and endothelial cells for angiogenesis and tissue remodeling and provides a matrix for cell migration [8,14].…”
Section: Introductionmentioning
confidence: 99%
“…The release of growth factors is high in the first few days then starts to slow down. With the aim of overcoming one of the main limitations of PRF and its degradation, an in vitro study was conducted on Alb-PRF, an injectable biomaterial, produced by PRF in liquid form and PPP heated to 75 degrees Celsius in 10 min with a device called APAG [ 187 , 195 , 196 , 197 ]. Since PPP is composed of 60% albumin, its denaturation creates an organized and dense protein structure without cells.…”
Section: Platelet Derivates and Growth Factorsmentioning
confidence: 99%
“…Since PPP is composed of 60% albumin, its denaturation creates an organized and dense protein structure without cells. This combination with APAG has been shown in vitro to preserve the volume and prolong the reabsorption times, leading to that the conclusion that the release of growth factors can continue much longer than in the traditional PRF [ 187 , 196 , 197 ]. The Alb-PRF preserves its volume even after 21 days [ 198 ]; however, the Alb-PRF membrane loses the elasticity of the PRF membrane and becomes very fragile.…”
Section: Platelet Derivates and Growth Factorsmentioning
confidence: 99%